VOCABULARY IN ESP APPLICATION AS REFLECTED TO THE LANGUAGE ACROSS CURRICULUM - Sumekto, Didik Rinan (MAGISTRA, 2012)
This paper discusses on the empirical experience of vocabulary instruction in English for specific purpose (ESP) as considered to the language across curriculum, particularly in mathematics course which stresses on syntax and semantics. ESP curriculum is relevantly designed to accommodate the specific needs of particular learners in groups, related to content, particular disciplines, occupations and activities, and centered on thelanguage appropriateness to relevant activities, such as syntax, lexis, discourse, and semantics. The issue of vocabulary instruction for English language learners (ELLs) concerns with productive, receptive, and recognition vocabulary where the one main goals of the instruction is to assist ELLs improve their comprehension in themultiple-choice tests, text comprehension, and process of understanding new meaning of words or phrases. Key words: English language learners, English for specific purpose, language across curriculum, vocabulary.